Na3V2(PO4)3/C composite as the intercalation-type anode material for sodium-ion batteries with superior rate capability and long-cycle life. Issue 16 (28th April 2015) - Wang, Dongxue; Chen, Nan; Li, Malin; Wang, Chunzhong; Ehrenberg, Helmut; Bie, Xiaofei; Wei, Yingjin; Chen, Gang; Du, Fei
<x xml:space="preserve">Abstract</x> Long-cycle stability with a capacity retention of 62% after 3000 cycles at a high charge rate of 10 C (2 A g−1).